2020
DOI: 10.1108/ijse-10-2019-0652
|View full text |Cite
|
Sign up to set email alerts
|

How psychological factors boost compulsive buying behavior in digital era

Abstract: PurposeTo find the root of the problem for compulsive buying behavior of students in the digital era by exploring psychological factors such as materialism, self-esteem, self-control, narcissism, money attitude and mood as boosters of the effect of income on compulsive buying behavior.Design/methodology/approachThe unit of analysis in this research was a group of students having experience using e-commerce. The data collection method in this study was a closed questionnaire with a scale of 1–5 agree–disagree i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
1
3
0
1
Order By: Relevance
“…Specifically, the finding whereby a low self-acceptance is associated with a higher probability of compulsive buying was consistent with those found by other researchers in the field [28,104] who note that a weak self-worth in combination with a lack in confidence in their ability to take on challenges and responsibilities entails an increased risk of engaging in "compensatory" behaviour. As to the restraining effect on compulsive buying which, according to our results, affiliation seems to have, there is previous empirical evidence as to the fact that compulsive buyers have significantly lower levels in agreeableness' facets (e.g., trust, straightforwardness, altruism) [84], greater narcissism [105,106] and negative family environment (i.e., higher family conflict and lower support) [107,108]. It could be hypothesised that this antagonistic interpersonal orientation may be reinforced, at least in part, by the emotional instability that makes relationships more difficult and less satisfactory.…”
Section: Discussionsupporting
confidence: 61%
“…Specifically, the finding whereby a low self-acceptance is associated with a higher probability of compulsive buying was consistent with those found by other researchers in the field [28,104] who note that a weak self-worth in combination with a lack in confidence in their ability to take on challenges and responsibilities entails an increased risk of engaging in "compensatory" behaviour. As to the restraining effect on compulsive buying which, according to our results, affiliation seems to have, there is previous empirical evidence as to the fact that compulsive buyers have significantly lower levels in agreeableness' facets (e.g., trust, straightforwardness, altruism) [84], greater narcissism [105,106] and negative family environment (i.e., higher family conflict and lower support) [107,108]. It could be hypothesised that this antagonistic interpersonal orientation may be reinforced, at least in part, by the emotional instability that makes relationships more difficult and less satisfactory.…”
Section: Discussionsupporting
confidence: 61%
“…Narcissists will have a strong need for admiration and recognition to meet subjective requirements, and anxiety will be generated when the needs are not met. In the study of Sedikides et.al in 2007, they found that narcissism will cause consumers to have compulsive buying behaviors, because it can verify narcissists' too positive self-belief [2]. This verification enables narcissists to bring the cognitive distance between self-belief and hypothetical reality and alleviate the anxiety caused by cognitive dissonance.…”
Section: Cognitive Dissonance Leading To Compulsive Behaviormentioning
confidence: 99%
“…Peneliti terdahulu menyebutkan bahwa perilaku compulsive buying juga merupakan hasil dari interaksi berbagai macam psychological factors yang dicirikan dengan high levels of materialism (Potrich & Vieira, 2018), low levels of self-esteem (Mulyono & Rusdarti, 2020), dan high levels of anxiety (Veludo-de-Oliveira et al, 2014). Materialism adalah konstruk psikologis yang mencerminkan sejauh mana seorang individu percaya bahwa penting untuk memiliki uang dan harta benda yang dapat menunjukkan citra dan status yang mereka inginkan (Kasser, 2018).…”
Section: Pendahuluanunclassified